A segurança da dependência e os desafios da soberania: expansão da agroindústria canavieira e a geografia do abastecimento alimentar no município de Tupi Paulista/SP - Valério, Valmir José de Oliveira [UNESP] (2015)
Different actors dispute specific forms of land use and management/control of territory, and contribute in the production of space in different ways, depending on their respective projects of society. These differences and territorial disputes are important to understand diverse models of development of the countryside: promoted by peasant agriculture and promoted by agribusiness, and in this case, specifically the sugarcane agribusiness. Given this, and using the concept of food sovereignty - the right of peoples to produce, in accordance with their own practices and cultural habits, the food for local consumption and markets - as a referential concept and point of departure, this project postulates the following hypothesis to be verified: the territorialization of sugarcane is resulting in more precarious conditions of production of other food crops destined for local and regional consumption, deepening dependence on the movement of food in space, aggravating the establishment of food sovereignty...